Carbonic Anhydrases as Potential Targets Against Neurovascular Unit Dysfunction in Alzheimer’s Disease and Stroke - Lemon, Nicole; Canepa, Elisa; Ilies, Marc A.; Fossati, Silvia (Frontiers in Aging Neuroscience, 2021)
The Neurovascular Unit (NVU) is an important multicellular structure of the central nervous system (CNS), which participates in the regulation of cerebral blood flow (CBF), delivery of oxygen and nutrients, immunological surveillance, clearance, barrier functions, and CNS homeostasis. Stroke and Alzheimer Disease (AD) are two pathologies with extensive NVU dysfunction. The cell types of the NVU change in both structure and function following an ischemic insult and during the development of AD pathology. Stroke and AD share common risk factors such as cardiovascular disease, and also share similarities at a molecular level. In both diseases, disruption of metabolic support, mitochondrial dysfunction, increase in oxidative stress, release of inflammatory signaling molecules, and blood brain barrier disruption result in NVU dysfunction, leading to cell death and neurodegeneration. Improved therapeutic strategies for both AD and stroke are needed. Carbonic anhydrases (CAs) are well-known targets for other diseases and are being recently investigated for their function in the development of cerebrovascular pathology. CAs catalyze the hydration of CO2 to produce bicarbonate and a proton. This reaction is important for pH homeostasis, overturn of cerebrospinal fluid, regulation of CBF, and other physiological functions. Humans express 15 CA isoforms with different distribution patterns. Recent studies provide evidence that CA inhibition is protective to NVU cells in vitro and in vivo, in models of stroke and AD pathology. CA inhibitors are FDA-approved for treatment of glaucoma, high-altitude sickness, and other indications. Most FDA-approved CA inhibitors are pan-CA inhibitors; however, specific CA isoforms are likely to modulate the NVU function. This review will summarize the literature regarding the use of pan-CA and specific CA inhibitors along with genetic manipulation of specific CA isoforms in stroke and AD models, to bring light into the functions of CAs in the NVU. Although pan-CA inhibitors are protective and safe, we hypothesize that targeting specific CA isoforms will increase the efficacy of CA inhibition and reduce side effects. More studies to further determine specific CA isoforms functions and changes in disease states are essential to the development of novel therapies for cerebrovascular pathology, occurring in both stroke and AD.